Genetics of Parkinson’s disease in Brazil: a systematic review of monogenic forms - Bruno L. Santos-Lobato; Artur Schumacher-Schuh; Ignacio F. Mata; Grace H. Letro; Pedro Braga-Neto; Pedro R. P. Brandão; Clécio O. Godeiro-Junior; Marcus V. Della Coletta; Sarah T. Camargos; Vanderci Borges; Carlos R. M. Rieder; Vitor Tumas (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Increasing numbers of mutations causing monogenic forms of Parkinson's disease (PD) have been described, mostly among patients in Europe and North America. Since genetic architecture varies between different populations, studying the specific genetic profile of Brazilian patients is essential for improving genetic counseling and for selecting patients for clinical trials. Objective: We conducted a systematic review to identify genetic studies on Brazilian patients and to set a background for future studies on monogenic forms of PD in Brazil. Methods: We searched MEDLINE, EMBASE and Web of Science from inception to December 2019 using terms for "Parkinson's disease", "genetics" and "Brazil". Two independent reviewers extracted the data. For the genes LRRK2 and PRKN, the estimated prevalence was calculated for each study, and a meta-analysis was performed. Results: A total of 32 studies were included, comprising 94 Brazilian patients with PD with a causative mutation, identified from among 2,872 screened patients (3.2%). PRKN mutations were causative of PD in 48 patients out of 576 (8.3%). LRRK2 mutations were identified in 40 out of 1,556 patients (2.5%), and p.G2019S was the most common mutation (2.2%). Conclusions: PRKN is the most common autosomal recessive cause of PD, and LRRK2 is the most common autosomal dominant form. We observed that there was a lack of robust epidemiological studies on PD genetics in Brazil and, especially, that the diversity of Brazil’s population had not been considered.